Field notes and letter from Tanya Bray to Thomas H. Kent regarding a sighting of an unusual looking duck, March 3, 1983 - Bray, Tanyaet al (1983)
Winter report of birds contributed by Tanya Bray. Also included is a letter from Bray to Thomas H. Kent regarding a sighting of an unusual looking duck. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of winter 1982-1983. Epson - sheet feed